Institutional determinants of ownership stake in cross‐border acquisitions in Africa: The moderating role of geographic distance. (14th December 2022) - Galdino, Katia M.; Ellis, Kimberly M.; Lamont, Bruce T.; Ariño, Africa
Abstract: We look at how emerging markets' institutional features affect ownership stake in cross‐border acquisitions (CBAs) within Africa. Particularly, we show that the presence of shared colonial history between the home and host country and the extent of fractionalization distance and formal institutional distance influence the acquiring firm's decision regarding its ownership stake in the target. Moreover, we show that geographic distance between the home and host country, by augmenting uncertainty faced by acquiring firms, moderates the relationship between these institutional features and ownership stake. We test our hypotheses in a sample of 341 intra‐Africa CBAs from 2001 to 2016. Generally, we find that greater ex ante uncertainty and ex post costs increase ownership stake. Specifically, greater geographic distance strengthens the positive relationship between shared colonial history and ownership stake and reverses the negative relationship between formal institutional distance and ownership stake. As for fractionalization distance, the relationship is more nuanced and needs to be further studied. We contribute to advance research on south–south CBAs in general, particularly within Africa, as well as to extend hostage theory in foreign market entry strategies in and from emerging markets.